Integrated Target Assignment and Trajectory Optimization for Many-to-Many Midcourse Guidance - Jin, Tianyu; Shin, Hyo-Sang; Tsourdos, Antonios; He, Shaoming (IEEE transactions on aerospace and electronic systems, 2025)
This article investigates the problem of target assignment and trajectory optimization in multimissile multitarget engagement scenarios. To avoid complex mixed-integer nonlinear programming problems, most of the existing methods solve the assignment and trajectory optimization separately, which cannot fully exploit the synthetic effect between these two functional blocks. To address this dilemma, we propose a new approach based on differential dynamic programming, which can solve assignment and trajectory optimization integrally instead of decoupling them. The proposed method embeds the target assignment problem into terminal constraints and adds the allocation matrix as parameters to the computational process of differential dynamic programming. In order to find the local optimal allocation scheme, a mixed-integer quadratic programming problem needs to be solved in each iteration. The advantages of the proposed method are that the allocation and trajectory optimization share the same objective function and are solved uniformly with an acceptable time consumption. Extensive numerical simulations and comparisons demonstrate the effectiveness of the proposed method.